THE ROLE OF ARTIFICIAL INTELLIGENCE SELF-EFFICIENCY IN IMPROVING THE QUALITY OF ACCOUNTING INFORMATION-AN APPLIED STUDY IN THE ELECTRICAL TRANSFORMER PRODUCTION PLANT IN SALAH AL-DIN (World Economics and Finance Bulletin, 2026)
The contemporary study aims to determine the role of artificial intelligence self-efficacy, through its dimensions (AI awareness, technological adaptability, and digital literacy), in the quality of accounting information, through its dimensions (reliability, relevance, stability, and comparability). This is an applied study conducted in the electrical transformer production plant in Salah al-Din. The research used the descriptive analytical method to achieve this objective. The sample size was (112) employees of the plant. The research was based on the main question: (Does artificial intelligence self-efficacy play a role in improving the quality of accounting information in the electrical transformer production plant in Salah al-Din?) The questionnaire was used as the main tool for data collection, and the numerical sequencers (AMOS.V.29, SPSS.V.29) were used. The exploration outcomes showed that the use of artificial intelligence techniques contributes to increasing the accuracy of accounting information by reducing human errors in recording and analyzing financial data.
Keywords: Artificial intelligence self-efficacy; accounting information quality